2011
DOI: 10.5194/hess-15-689-2011
|View full text |Cite
|
Sign up to set email alerts
|

The influence of soil moisture on threshold runoff generation processes in an alpine headwater catchment

Abstract: Abstract. This study investigates the role of soil moisture on the threshold runoff response in a small headwater catchment in the Italian Alps that is characterised by steep hillslopes and a distinct riparian zone. This study focuses on: (i) the threshold soil moisture-runoff relationship and the influence of catchment topography on this relation; (ii) the temporal dynamics of soil moisture, streamflow and groundwater that characterize the catchment's response to rainfall during dry and wet periods; and (iii)… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

41
303
4
2

Year Published

2012
2012
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 370 publications
(378 citation statements)
references
References 39 publications
41
303
4
2
Order By: Relevance
“…The absence of a straightforward relationship between monthly values of rainfall and water yield is not particular to the data shown here, and a similar effect has already been reported for humid temperate catchments (Endale et al 2006, Merz et al 2006, Penna et al 2011) and for Mediterranean catchments (GarcĂ­a-RuĂ­z et al 2008), in particular. A possible factor explaining this nonlinearity is related to the number, the succession and the characteristics of the rainfall events, as well as to the seasonal dynamics of rainfall and evapotranspiration, which then affect the antecedent conditions for individual rainfall events.…”
Section: Overview Of Hydrological Responsesupporting
confidence: 55%
See 2 more Smart Citations
“…The absence of a straightforward relationship between monthly values of rainfall and water yield is not particular to the data shown here, and a similar effect has already been reported for humid temperate catchments (Endale et al 2006, Merz et al 2006, Penna et al 2011) and for Mediterranean catchments (GarcĂ­a-RuĂ­z et al 2008), in particular. A possible factor explaining this nonlinearity is related to the number, the succession and the characteristics of the rainfall events, as well as to the seasonal dynamics of rainfall and evapotranspiration, which then affect the antecedent conditions for individual rainfall events.…”
Section: Overview Of Hydrological Responsesupporting
confidence: 55%
“…5 it is clear that, as the catchment becomes wet, the hydrological response increases and, consequently, it represents a greater percentage of rainfall. Probably the antecedent soil moisture state plays an important role in the hydrological response of the catchment, as has been often suggested for temperate humid catchments (Dunne et al 1975, Pfister et al 2002, Norbiato et al 2009, Penna et al 2011. However, over the study period, the observed seasonality of the runoff coefficients was also possibly affected by rainfall characteristics, such as large and long rainfall events occurring in 2006.…”
Section: Hydrological Response At the Event Scalementioning
confidence: 67%
See 1 more Smart Citation
“…Our study underpins the expedience of using tensiometers in place of TDR probes, which are commonly used (Brocca et al, 2007;Penna et al, 2011;Zehe et al, 2010) to assimilate soil moisture into rainfall-runoff modeling. Our analysis shows that further studies on flood forecasting should concentrate on carefully selecting representative measurement sites to improve the quality of forecasts instead of labor-intensive and costly attempts to monitor the soil moisture of an entire catchment.…”
Section: Resultsmentioning
confidence: 99%
“…Using a hydrological model for an evaluation of climate model results also enables the incorporation of other hydrological 25 quantities, which give indications about the performance of the climate model regarding the hydrological conditions. Soil moisture is an important variable to be analysed in terms of non-linearity and threshold processes in flood generation (e.g., Penna et al, 2011). It is continuously calculated by the hydrological model, and hence, can be used as a comparison between the different simulation runs.…”
Section: Evaluation Measuresmentioning
confidence: 99%